The news revolution in England : cultural dynamics of daily information - Sommerville, C. John (Charles John), 1938- (Oxford University Press, 1996)
The News Revolution in England: Cultural Dynamics of Daily Information is the first book to analyze the essential feature of periodical media, which is their periodicity. Having to sell the next issue as well as the present one changes the relation between authors and readers--or customers--and subtly shapes the way that everything is reported, whether politics, the arts and science, or social issues. So there are certain biases that are implicit in the dynamics of news production or commodified information, quite apart from the intentions of journalists. With the birth of the commercial perio.